Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

The xyloglucan galactosylation modulates the cell wall stability of pollen tube - Qiqi Wei; Ying Yang; Hui Li; Zhiwen Liu; Rong Fu; Hanqian Feng; Chao Li (Planta, 2021)

Seasonal prediction skills in the CAMS-CSM climate forecast system - Bo Liu; Jingzhi Su; Libin Ma; Yanli Tang; Xinyao Rong; Jian Li; Haoming Chen; Boqi Liu; Lijuan Hua; Renguang Wu (Climate Dynamics, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Molecular cloning of myosin chaperone uncoordinate-45B (UNC-45B) and its heat stress response in the muscle of Pacific bluefin tuna Thunnus orientalis - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Uno Yamashita; Yan-Rong Jiang; Xiao-Mi Sun; Kazuya Shirota; Yasuhiko Shiina; Kiyoshi Osatomi (Fisheries Science, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

AsTal1 from Aquilaria sinensis regulates ABA signaling-mediated seed germination and root growth in Nicotiana benthamiana - Yuqing Rong; Tiezheng Li; Xiao Liu; Shepo Shi; Xiaohui Wang; Pengfei Tu (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

CARMA1 is required for Notch1-induced NF-κB activation in SIL-TAL1-negative T cell acute lymphoblastic leukemia - Ninghan Zhang; Jiawen Xu; Rong Wang; Ting Pan; Huanxin Zhang; Lingling Yin; Yao Yao; Linyan Xu; Shengyun Zhu; Qingyun Wu; Zhenyu Li; Xuejiao Liu; et al. (Journal of Molecular Medicine, 2021)

Circular RNA circ_Cabin1 promotes DNA damage in multiple mouse organs via inhibition of non-homologous end-joining repair upon PM2.5 exposure - Huixian Zeng; Meizhen Li; Qiuhan Hua; Yufei Liu; Yueting Shao; Qinqin Diao; Yihui Ling; Han Zhang; Miaoyun Qiu; Jialu Zhu; Xun Li; Rong Zhang; et al. (Archives of Toxicology, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Enhanced Biodegradation of Hexachlorocyclohexane in Soil by Application of Exogenous Amendments - Xutong Liu; He Huang; Dan Huang; Kai Zhong; Qun Rong; Xingzi Qin; Chaolan Zhang; Xue Li (Water, Air, & Soil Pollution, 2021)

Recombinant L-HN Fusion Antigen Derived from the L and HN Domains of Botulinum Neurotoxin B Stimulates a Protective Antibody Response Against Active Neurotoxin - Zhen Li; Jian-Sheng Lu; Shan Liu; Rong Wang; Qing Xu; Yun-Zhou Yu; Zhi-Xin Yang (Neurotoxicity Research, 2021)

Exposure to antibiotics and mental disorders in children: a community-based cross-sectional study - Jingjing Zhang; Kaiyong Liu; Liang Sun; Linsheng Yang; Xinji Liu; Yitian Zhu; Rong Wei; Zhongxiu Jin; Li Wang; Ying Ma; Sufang Wang; Annuo Liu; et al. (Environmental Geochemistry and Health, 2021)

Dissipation, residue, dietary, and ecological risk assessment of atrazine in apples, grapes, tea, and their soil - Longfei Yuan; Yida Chai; Congdi Li; Rong Liu; Zenglong Chen; Li Li; Wei Li; Yujian He (Environmental Science and Pollution Research, 2021)

Cooperation Search Algorithm for Power Generation Production Operation Optimization of Cascade Hydropower Reservoirs - Wen-jing Niu; Zhong-kai Feng; Yu-rong Li; Shuai Liu (Water Resources Management, 2021)

MiR-146a Negatively Regulates Aspergillus fumigatus-Induced TNF-α and IL-6 Secretion in THP-1 Macrophages - Jianbo Tong; Zhimin Duan; Rong Zeng; Leilei Du; Song Xu; Liwei Wang; Yuzhen Liu; Qing Chen; Xu Chen; Min Li (Mycopathologia, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Response of Terrigenous Sediment Input to Sea Level Change and East Asian Monsoon Evolution Since 30kyr in the Southwestern Taiwan Basin - Li Feng; Xiuli Feng; Rong Tang; Xiao Xiao; Jie Liu (Journal of Ocean University of China, 2021)

Isolation and identification of antimicrobial metabolites from sea anemone-derived fungus Emericella sp. SMA01 - Yang Yue; Huahua Yu; Rongfeng Li; Linfeng Hu; Song Liu; Rong’e Xing; Pengcheng Li (Journal of Oceanology and Limnology, 2021)

Clinical study on empirical and diagnostic-driven (pre-emptive) therapy of voriconazole in severe aplastic anaemia patients with invasive fungal disease after intensive immunosuppressive therapy - Yuhong Wu; Li Yan; Huaquan Wang; Hong Liu; Limin Xing; Rong Fu; Zonghong Shao (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Molecular Characterization of Hsp47 in Grass Carp (Ctenopharyngodon idella) and Its Correlation with Type I Collagen in Response to Fish Aerobic Exercise - Xiao Liang; Ying Wan; Zhiyuan Shen; Yanmei Liu; Dapeng Li; Li Li; Rong Tang; Xi Zhang (Fishes, 2021)
Heat shock protein 47 (Hsp47) is a collagen-specific molecular chaperone that is indispensable for molecular maturation of collagen. In this study, hsp47 and hsp47-like cDNAs were cloned and characterized in grass carp (Ctenopharyngodon idella). The cDNAs were 1212 and 1218 base pairs long, respectively, and included an open reading frame encoding 403 and 405 amino acids. The molecular phylogeny based on the deduced amino acid sequences indicated that the correct sequences of the hsp47 and hsp47-like cDNA were obtained and the deduced proteins clustered distinctly into teleost clades. Primary structure analysis and characterization of Hsp47 and Hsp47-like shared the basic structure and biofunctions of Hsp47 in vertebrates. The spatial pattern of gene expression revealed that hsp47 and hsp47-like were relatively ubiquitous in different tissues and highly expressed in heart and skin. The expression levels of hsp47 and hsp47-like and type I collagen mRNAs varied similarly in different tissues. Type I collagen content increased significantly with the increase of water velocity in the muscle of grass carp in response to aerobic exercise. Among the gene expression changes of hsp47, hsp47-like, col1a1 and col1a2 in muscle that occurred in response to aerobic exercise, the change of type I collagen was most strongly correlated with hsp47 expression. Additionally, col1a1 showed the highest correlation with hsp47-like and col1a2 showed the highest correlation with hsp47. These findings suggest that grass carp Hsp47 and Hsp47-like are closely related to type I collagen synthesis. This study firstly suggests fish aerobic exercise can improve type I collagen content and Hsp47 gene expression in muscle of grass carp.

Isolation, culture, and characterization of cells derived from giant panda (Ailuropoda melanoleuca) semen - Yuliang Liu; Yuan Li; Rong Hou; Zhigang Cai; Donghui Wang; Jiasong Chen; Feiping Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2021)

High stocking density alters growth performance, blood biochemical profiles, and hepatic antioxidative capacity in gibel carp (Carassius gibelio) - Kommaly Onxayvieng; Marina Piria; Mirna Mrkonjić Fuka; Ana Gavrilović; Xiao Liang; Lu Liu; Rong Tang; Li Li; Dapeng Li (Fish Physiology and Biochemistry, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Effect of bFGF on fibroblasts derived from the golden snub-nosed monkey - Xin Liu; Hao Wei; Jing Yang; Jingjing Li; Pei Zhang; Yuli Li; Rong Hou; Jinlian Hua; Xingrong Yan; Baoguo Li (Primates, 2021)

Neobacillus sedimentimangrovi sp. nov., a Thermophilic Bacterium Isolated from Mangrove Sediment - Rong Tang; Qi Zhang; Manik Prabhu Narsing Rao; Guo-Hong Liu; Jian-Mei Che; Min Lei; Bo Liu; Wen-Jun Li; Shun-Gui Zhou (Current Microbiology, 2021)

Accumulation and Depuration of Cd and its Effect on the Expressions of Metallothionein and Apoptotic Genes in Litopenaeus vannamei - Ling Li; Yu-Chun Shen; Jin-Rong Liang; Hu Liu; Tian-Ci Chen; Hui Guo (Bulletin of Environmental Contamination and Toxicology, 2021)

Influence of the roots of mixed-planting species on the shear strength of saline loess soil - Ya-bin Liu; Xia-song Hu; Dong-mei Yu; Hai-li Zhu; Guo-rong Li (Journal of Mountain Science, 2021)

Knockdown of Arginyl-tRNA Synthetase Attenuates Ischemia-Induced Cerebral Cortex Injury in Rats After Middle Cerebral Artery Occlusion - Yang Liu; Xue-Bin Hu; Li-Zhi Zhang; Zi Wang; Rong Fu (Translational Stroke Research, 2021)
Some researchers have previously shown that RNAi knockdown of arginyl-tRNA synthetase (ArgRS) before or after a hypoxic injury can rescue animals from death, based on the model organism, C. elegans . However, there has been no study on the application of arginyl-tRNA synthetase knockdown in treating mammalian ischemic stroke, and its potential mechanism and effect on ischemic brain damage are still unknown. Here, we focused on the Rars gene, which encodes an arginyl-tRNA synthetase, and examined the effects of Rars knockdown in a permanent middle cerebral artery occlusion model in rats. To achieve this aim, adult male Sprague-Dawley (SD) rats were given right cerebral cortex injections of short hairpin RNA (shRNA) adenovirus (AV) particles to knock down arginyl-tRNA synthetase, and a non-targeting control (NTC) vector or phosphate-buffered solution served as the controls. After 4 days, the rats were exposed to permanent middle cerebral artery occlusion (pMCAO). Then, the right cerebral cortex level of arginyl-tRNA synthetase was examined, and the effects of the Rars knockdown were evaluated by differences in infarction volume, oxidative stress, blood-brain barrier, mitochondrial function, and glucose metabolism at 1 day and 3 days after MCAO. The injection of shRNA adenovirus particles successfully suppressed the expression of arginyl-tRNA synthetase in the cerebral cortex. We observed an improvement in oxidative stress, mitochondrial function, and glucose utilization and a reduction in brain edema compared with the non-targeting control rats with suppressed expression of arginyl-tRNA synthetase mRNA in the ipsilateral ischemic cortex of the brain. Our findings indicate that knockdown of arginyl-tRNA synthetase in the cerebral cortex exerted neuroprotective effects, which were achieved not only by the improvement of oxidative stress and glucose utilization but also by the maintenance of mitochondrial morphological integrity and the preservation of mitochondrial function. Knockdown of ArgRS administration could be a promising approach to protect ischemic stroke.

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Paeonol ameliorates CFA-induced inflammatory pain by inhibiting HMGB1/TLR4/NF-κB p65 pathway - Chen Qiu; Liu-Di Yang; Wen Yu; Dan-Dan Tian; Mei-Rong Gao; Wen-Ju Wang; Xu-Bo Li; Yu-Mei Wu; Min Wang (Metabolic Brain Disease, 2021)

Selenium Deficiency via the TLR4/TRIF/NF-κB Signaling Pathway Leading to Inflammatory Injury in Chicken Spleen - Ruili Zhang; Rong Guo; Qing Liu; Guangxing Li; Bin Sun; Xiaodan Huang (Biological Trace Element Research, 2021)

Climate‐induced nonlinearity in pelagic communities and non‐stationary relationships with physical drivers in the Kuroshio ecosystem - Shuyang Ma; Yongjun Tian; Caihong Fu; Haiqing Yu; Jianchao Li; Yang Liu; Jiahua Cheng; Rong Wan; Yoshiro Watanabe (Fish and Fisheries, 2021)
Climate‐induced nonlinearity in biological variability and non‐stationary relationships with physical drivers are crucial to understand responses of marine organisms to climate variability. These phenomena have raised concerns in the northeastern North Pacific, but are out of the spotlight in the northwestern North Pacific in spite of potential implications for this productive system under increased climate variability. Pelagic communities in the Kuroshio ecosystem have both ecological and economic importance. However, patterns of climate‐induced nonlinearity in pelagic communities are not well understood, and existence of non‐stationarity in their relationships with physical drivers remains obscure. Here, we compile large numbers of climatic, oceanic and biological long‐term time‐series data and employ diverse statistical techniques to reveal such climate‐induced nonlinearity and non‐stationarity. Results show that pelagic communities in the Tsushima and Pacific areas (major areas in the Kuroshio ecosystem) had regime shifts in the late 1990s and late 1980s, respectively. Winter sea surface temperatures in the Kuroshio Current path and in the eastern part of East China Sea, which are respectively affected by the Kuroshio Current and Siberian High, correlate with dominant variability patterns in their pelagic communities. Furthermore, non‐stationarity was identified with threshold years in the 1990s in the Tsushima area and in the 1980s in the Pacific area as a possible result of the declined variances in the Siberian High and Aleutian Low, respectively. Our findings provide insights on spatial differentiation of climate‐induced nonlinearity and non‐stationarity, which are valuable for the management of pelagic communities in the northwestern North Pacific under changing climatic conditions.